Students’ perspectives on technology integration in ELT - Singh, Renu (Journal of NELTA, 2019)
Technology integration in English language teaching (ELT) has changed the mode of classroom instruction at school. The use of modern technologies at public secondary schools within Nepal is a big challenge. This study explores students ‘perspectives on technology integration in English language teaching at public secondary schools in Nepal. The study was framed under qualitative research design that used focus group discussion to gather data from the six groups of students in the Kathmandu valley. The thematic analysis of their views under different categories revealed that the ELT with technology integration is a dire need for developing students’ language proficiency. Additionally, the results show that the learners of English as a foreign language (EFL) are aware of the advantages of teaching with technology but the insufficient ICT infrastructure at school and the lack of EFL teachers’ professional skills and knowledge of integrating technology into their daily pedagogical practices are main obstacles of technology integration. The study points out implications for ELT practitioners, researchers, policy makers of ICT in education along with stakeholders.